2013
DOI: 10.1177/0305735613482024
|View full text |Cite
|
Sign up to set email alerts
|

How music changes our lives: A qualitative study of the long-term effects of intense musical experiences

Abstract: Intense musical experiences (IMEs) have proven to be of high significance for the people who have them. We investigated the long-term effects of such experiences on people’s way of life and developed a process model: (1) IMEs are characterized by altered states of consciousness, which leads to the experience of harmony and self-realization; (2) IMEs leave people with a strong motivation to attain the same harmony in their daily lives; (3) people develop manifold resources during an IME; (4) IMEs cause long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…The potential for music to provide routes to wellbeing other than pleasure is supported by two recent qualitative studies (Lamont, 2011;Schafer, Smukalla, & Oelker, 2014), where it was found that, in addition to pleasure, both absorption and transcendence were commonly reported experiences in response to music listening. …”
Section: Psychology Of Music 0(0)mentioning
confidence: 95%
See 1 more Smart Citation
“…The potential for music to provide routes to wellbeing other than pleasure is supported by two recent qualitative studies (Lamont, 2011;Schafer, Smukalla, & Oelker, 2014), where it was found that, in addition to pleasure, both absorption and transcendence were commonly reported experiences in response to music listening. …”
Section: Psychology Of Music 0(0)mentioning
confidence: 95%
“…Similarly, although some studies report a selective preference for positive over negative information, or positivity bias in older adults (Mather, 2005), other studies suggest that the major difference between younger and older adults may be in the reduction in negative affect and relative stability of positive affect in old age (Mroczek, 1998). Therefore, as positive emotion remains important throughout adult development, we do not anticipate less affective FML among older adults in general, but a stronger emphasis on positive relative to negative affordances of music listening in older relative to younger adults.Finally, like positive emotion, transcendence is a core virtue highlighted by positive psychology (Peterson & Seligman, 2004), and has been reported in music listening experiences (Lamont, 2011;Schafer et al, 2014). It has been suggested that due to a greater awareness of their mortality and an accompanying need to find meaning older adults have a greater sense of transcendence and spend more time seeking it (Piedmont, 1999), so it is possible that listening to music for transcendence and meaning is more common in older adults when compared with younger adults.…”
mentioning
confidence: 99%
“…On the other hand, when listeners are captivated or absorbed by music or have very intense or exceptional experiences (see protracted duration) “time will be experienced in the present as passing slowly but may be retroactively interpreted as having passed quickly” (Holmer Nadesan, 2002, p. 259). In addition, this effect can change when the experiences made are strong enough to leave traces in episodic memory, which would lead to the experience being retroactively interpreted as having lasted longer (see also Croom, 2012; Schäfer et al, 2013; for an overview about music and engagement).…”
Section: Music and The Representation Of Timementioning
confidence: 99%
“…A peak experience is an intricate, transcendent, and intense experience that is crucial for the development of the person. Intense musical experiences can result in lasting changes in a person's values, social relationships, and development [7].…”
Section: The Emotional Qualities Of Sound and Musicmentioning
confidence: 99%